Producción audiovisual y la difusión turística del centro histórico de la cuidad de Guaranda, provincia Bolívar, periodo 2013-2014 - Amangandi Gavilanes, Wilfrido Gonzalo (2014)
This grading work is derived from the realization of a series of tourism promotion and audiovisual products distribution, which is a basic communication tool and to generate diverse cultural processes. It is necessary, in this graduation work left writing that the journalist's role is critical to building communication processes within any government department, as it is the main source of information and communication, so to publicize and develop new ideas and projects. Chapter I includes: Theme, Background, problem formulation, justification, that their look has the need, timing, interest in the subject, objectives, theoretical framework, Marco Georeferencial, with the geographic location of the research Framework, referring to the most relevant concepts involving this research, Scientific Framework with theoretical aspect understood that frames this work. Chapter II contains the data in tables and graphs of statistical surveys of people living and often pass through the historic center of the city of Guaranda, after obtaining the respective tabulation of these data, and then make the Analysis and interpretation of results, and thereby reach conclusions, recommendations and hypothesis testing. Chapter III contains the Proposal, is conducting a series of audiovisual productions divided into three installments. These vary between 1 and 3 minutes each lasting about to be broadcast on the television channel of the corner, turn on television media, in the waiting rooms of public institutions, restaurants terminals etc.